Cognitive tasks during expectation affect the congruency ERP effects to facial expressions - Lin, Huiyan; Schulz, Claudia; Straube, Thomas (Frontiers in Human Neuroscience, 2015)
Expectancy congruency has been shown to modulate event-related potentials (ERPs) to emotional stimuli, such as facial expressions. However, it is unknown whether the congruency ERP effects to facial expressions can be modulated by cognitive manipulations during stimulus expectation. To this end, electroencephalography (EEG) was recorded while participants viewed (neutral and fearful) facial expressions. Each trial started with a cue, predicting a facial expression, followed by an expectancy interval without any cues and subsequently the face. In half of the trials, participants had to solve a cognitive task in which different letters were presented for target letter detection during the expectancy interval. Furthermore, facial expressions were congruent with the cues in 75% of all trials. ERP results revealed that for fearful faces, the cognitive task during expectation altered the congruency effect in N170 amplitude; congruent compared to incongruent fearful faces evoked larger N170 in the non-task condition but the congruency effect was not evident in the task condition. Regardless of facial expression, the congruency effect was generally altered by the cognitive task during expectation in P3 amplitude; the amplitudes were larger for incongruent compared to congruent faces in the non-task condition but the congruency effect was not shown in the task condition. The findings indicate that cognitive tasks during expectation reduce the processing of expectation and subsequently, alter congruency ERP effects to facial expressions.